Recurrent Wheezing and Asthma After Respiratory Syncytial Virus Bronchiolitis - Zhou, Yunlian; Tong, Lin; Li, Mengyao; Wang, Yingshuo; Li, Lanxin; Yang, Dehua; Zhang, Yuanyuan; Chen, Zhimin (Frontiers in Pediatrics, 2021)
Background: Respiratory syncytial virus (RSV) is the most common pathogen of acute bronchiolitis in children, which sometimes triggers the development of recurrent wheezing and increases the risk of childhood asthma. Methods: We enrolled 425 children who were diagnosed with RSV-infected bronchiolitis at the department of pulmonology, Children's Hospital Zhejiang University School of Medicine in 2011. Long-term follow-up was performed to explore the consequence of bronchiolitis on subsequent recurrent wheezing and asthma. Results: Of 425 patients, 266 cases completed the entire follow-up, the mean age of onset was 4.9 (3.3) months, and the male-to-female ratio was 2.5. The mean birth weight of all patients was 3.22 (0.63) kg, and the number of patients who had a history of cesarean section was 148. According to the outcome of follow-up, 36 were in the recurrent wheezing (RW) group, 65 were in the asthma (AS) group, and the remaining 165 were in the completely recovered (CR) group. The age of onset was older and the birth weights were higher in the AS group than those in the CR group (P<0.05). And the higher proportion of cesarean sections was higher in the RW group than that in the CR group (P<0.05). Furthermore, we found a remarkable increasing of serum IgE in the AS groups than that in the CR group (P <0.01). Multiple logistic regression analysis showed that the cesarean section was the risk factor for the development of recurrent wheezing and the higher birth weight was the risk factor for the development of asthma. Conclusion: RSV bronchiolitis might increase the incidence of recurrent wheezing and asthma. Allergic constitution was an important prerequisite for the occurrence of asthma, and related risk factor such as caesarean section can only increase recurrent wheezing to a certain extent within a certain period of time. And we also find higher birth weight and older onset age for those who develop asthma, which should be verified in the future.